DESIGN AND DEVELOPMENT OF TANK/VOLUME LEVEL AUTOMATION SYSTEM USING TOF (TIME OF FLIGHT) SENSOR BASED ON ARDUINO - Yohan Wibisono; Bambang Setiawan; Noor Sulistiyono; Dadang Abdul Aziz; Firmansyah Abdullah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2022)
Fuel oil is a primary need for the community to assist mobility activities in daily life. The role of fuel oil until now is an energy source that has become the main choice for use in various sectors, especially in shipping, it is a must as a transportation operator to monitor the availability of fuel oil on ships so that shipping traffic runs smoothly between lands. With the rapid development of technology in the current era of globalization, it has provided many benefits in progress in various aspects. The use of technology by humans in helping to complete work is a must in life. The development of this technology must also be followed by developments in Human Resources (HR). Humans as technology users must be able to take advantage of current technology, as well as subsequent technological developments. Human adaptation to new technologies that have developed must be done through innovation. The Time of Flight sensor is an electronic component that functions to measure the distance between the sensor and the object. In this study, use this for the purposes of measuring the level of the fuel tank on the ship. Thus, it can determine the level of the fuel level in the tank so that there is no oil spill, so that it can be monitored using Arduino.